The Effectiveness of the Teams Games Tournament (TGT) Cooperative Learning Model in Enhancing Pancasila Education Learning Motivation Among Eleventh Grade Students at SMK Negeri 5 Sidrap - Abiyyu Arib Mahyiyuddin; Anis Pacinnongi; Huser Huser; Erlita Erlita (Edumaspul: Jurnal Pendidikan, 2025)
Learning motivation is a key factor in educational success, particularly in Pancasila Education, which aims to develop moral character, critical thinking skills, and social responsibility among students. However, many students face difficulties in understanding and actively participating in Pancasila Education, as evidenced by low learning motivation. This study aims to explore the effectiveness of the Teams Games Tournament (TGT) cooperative learning model in enhancing the learning motivation of eleventh-grade students at SMK Negeri 5 Sidrap. The research method used is Classroom Action Research (CAR) with a one-group pre-test and post-test design. Data was collected from 25 students through observation and a learning motivation test, which were then analyzed using the Wilcoxon test. The results show that the implementation of the TGT model significantly increased students' learning motivation, with a z-value of -4.392 and a significance value of 0.000. This study confirms that the TGT model creates a more engaging, interactive, and collaborative learning environment, which boosts students' motivation and involvement in Pancasila Education. The implication of this study is that this model can serve as an alternative, effective learning strategy to enhance learning motivation among vocational school students. Keywords: Learning Motivation, Cooperative Learning, Teams Games Tournament, Pancasila Education